PERANCANGAN MEDIA PEMBELAJARAN BERBASIS GAME ANDROID PADA MATA PELAJARAN INFORMATIKA KELAS VII DI SMP INSAN TELADAN - Mohamad Alfin Fisar; Yasin Efendi; Mahbubul Wathoni; Rikaro Ramadi (LPPM Universitas Islam Darul `Ulum Lamongan, 2026)
The purpose of this study was to design an Android game-based learning medium for Informatics subjects at Insan Teladan Middle School.The method used in this research was Research and Development (R&D) with the Game Development Life Cycle (GDLC) model. This development model includes 6 phases: initialization/concept creation, pre-production, production, testing, beta, and release. This research was conducted at Insan Teladan Middle School with a trial subject of 23 seventh-grade students. The data collection technique used was a questionnaire assessed by media experts, subject matter experts, teachers, and students. The results of the assessment by the experts included an average score of 86% from media experts, 80% from subject matter experts, and 88% from teacher responses, all in the